Physical Activity, Sports Practice, and Cognitive Functioning: The Current Research Status - Hernández-Mendo, Antonio; Reigal, Rafael E.; López-Walle, Jeanette M.; Serpa, Sidonio; Samdal, Oddrun; Morales-Sánchez, Verónica; Juárez-Ruiz de Mier, Rocío; Tristán-Rodríguez, José L.; Rosado, António F.; Falco, Coral (Frontiers in Psychology, 2019)
The evidence for the benefits of physical activity on cognitive functioning has increased in recent years. Although the relationship between these variables has been analysed for decades, the development of evaluation techniques has resolved several issues and advanced this area of knowledge. Moreover, several authors have pointed out the association between the cognitive functioning of athletes and their performance in competition. These recent studies suggest that some specific cognitive abilities of athletes could help them become more effective and improve their chances of success. The objective of this paper was to identify the most relevant advances in these areas of study and to highlight more promising lines of research for the next few years. We discuss findings from the application of different physical activity programs as well as the most significant cognitive performance variables for sports practice. In addition, the limitations of the findings are discussed.